Evaluation of Antioxidant Activity in Lemon Juice (Citrus limon) Marketed in Makassar City Using the DPPH (2,2 diphenyl-1-picrylhydrazyl) Method - A Saad Asmawati; Rahmi Rahmi; Desi Reski Fajar; Ira Widya Sari (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Human lifestyle is currently experiencing many changes that lead to unhealthy lifestyles. An instant lifestyle can trigger degenerative diseases, which are initiated by excessive oxidation reactions in the body, which can cause the formation of free radicals. Lemon juice, derived from the Citrus limon plant, is considered a functional beverage due to its antioxidant properties, which have the potential to counteract the harmful effects of free radicals. This study aimed to measure the antioxidant activity of lemon juice beverage based on the IC50 value. The present study adopted a descriptive laboratory approach, utilizing lemon juice beverages from three distinct brands as representative samples. The antioxidant activity test was carried out by adding DPPH and measured using UV-Vis Spectrophotometry. The antioxidant levels obtained were 1,091.17 µg/mL for sample A, 1,114.50 µg/mL for sample B, and 527,261 µg/mL for sample C. All samples exhibited antioxidant activity values that fell within the